2016
DOI: 10.1039/c6dt00143b
|View full text |Cite
|
Sign up to set email alerts
|

K2Sn2ZnSe6, Na2Ge2ZnSe6, and Na2In2GeSe6: a new series of quaternary selenides with intriguing structural diversity and nonlinear optical properties

Abstract: Three new compounds (i.e., K2Sn2ZnSe6, Na2Ge2ZnSe6, and Na2In2GeSe6) with intriguing structural diversity and nonlinear optical properties were discovered for the first time. They crystallize in space groups P4/ncc, I4/mcm and Cc, respectively. In K2Sn2ZnSe6 and Na2Ge2ZnSe6, the [Sn(Ge)Se4] tetrahedra and [ZnSe4] tetrahedra are linked via edge-sharing to build up a 1D [Sn2ZnSe6] infinite chain separated by K(+)(Na(+)) cations along the c direction, while the structure of Na2In2GeSe6 is an interesting three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 35 publications
(33 reference statements)
3
18
0
Order By: Relevance
“…The lengths of the Li−Se bonds range from 2.51(10) to 2.59(3) Å, which are shorter than 2.64(3) to 2.83(3) Å in LiGaGe 2 Se 6 and 2.61(1) to 2.86(2) Å in Li 2 In 2 SiSe 6 . The Sn−Se bond lengths vary from 2.5114(4) to 2.5249(17) Å, which are consistent with those for tetrahedrally coordinated Sn in K 2 MnSnSe 4 (2.516(1) to 2.525(1) Å) and K 2 Sn 2 ZnSe 6 (2.4986(8) to 2.5672(7)) Å . As for the (Li/Mn)−Se bond lengths, they range from 2.512(3) to 2.586(8) Å, comparable to the values of Li−Se (2.5963 Å in Li 2 Se) and Mn−Se (2.3087 Å in MnSe) bond lengths.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The lengths of the Li−Se bonds range from 2.51(10) to 2.59(3) Å, which are shorter than 2.64(3) to 2.83(3) Å in LiGaGe 2 Se 6 and 2.61(1) to 2.86(2) Å in Li 2 In 2 SiSe 6 . The Sn−Se bond lengths vary from 2.5114(4) to 2.5249(17) Å, which are consistent with those for tetrahedrally coordinated Sn in K 2 MnSnSe 4 (2.516(1) to 2.525(1) Å) and K 2 Sn 2 ZnSe 6 (2.4986(8) to 2.5672(7)) Å . As for the (Li/Mn)−Se bond lengths, they range from 2.512(3) to 2.586(8) Å, comparable to the values of Li−Se (2.5963 Å in Li 2 Se) and Mn−Se (2.3087 Å in MnSe) bond lengths.…”
Section: Resultssupporting
confidence: 66%
“…[5c] The SnÀSe bond lengths vary from 2.5114(4) to 2.5249 (17) ,w hich are consistent with those for tetrahedrally coordinated Sn in K 2 MnSnSe 4 (2.516(1)t o2 .525(1) ) [14] and K 2 Sn 2 ZnSe 6 (2.4986(8) to 2.5672 (7)) . [15] As for the (Li/Mn)ÀSe bond lengths, they range from 2.512(3) to 2.586 (8) ,c omparable to the valueso fL i ÀSe (2.5963 in Li 2 Se) [16] and MnÀSe (2.3087 in MnSe) [17] bond lengths.…”
Section: Crystal Structurementioning
confidence: 73%
“…They crystallize in the noncentrosymmetrics pace group Selected bond lengths for the title compounds are listed in Ta ble S1.F or Li 7 (17) ) [36] and K 2 Sn 2 ZnSe 6 (2.4986(8)-2.5672 (7) ). [37] For the two title compounds, the CdÀSe bond lengths vary from 2.570(2) to 2.653(3) ,w hich is in good agreement with the values of 2.360(3) to 2.900(4) in La 3 CdGaSe 7 [38] and2 .609(2) to 2.631 (2) in CsCdInSe 3 . [39] The (Li/Cd)ÀSe bond lengths range from 2.314(19) to 2.750 (12) ,w hichi sc omparable to the valueso fLi ÀSe and CdÀSe bond lengths mentioned above.…”
Section: Introductionsupporting
confidence: 63%
“…The Li atoms in distorted tetrahedral coordination (Li@S 4 ) form an infinite chain parallel to the c axis by vertex-sharing. K 2 Sn 2 ZnSe 6 and Na 2 Ge 2 ZnSe 6 ( [11], Fig. 3b and c) .…”
Section: Resultsmentioning
confidence: 97%
“…The substitution of In for Ga results in a series of compounds Li 2 In 2 Si(Ge)S 6 (Se 6 ) that crystallize in a monoclinic structure, space group Cc [8,9]. Isostructural sodium-containing compounds Na 2 In 2 Si(Ge)S 6 (Se 6 ) and Na 2 CdGe 2 S 6 (Se 6 ) have also been reported [10][11][12][13]. It has been found that Na 2 Ga 2 GeS 6 crystallizes in the orthorhombic structure (space group Fdd2), while Na 2 In 2 SiS 6 and Na 2 In 2 GeS 6 have monoclinic structures (space group Cc).…”
Section: Introductionmentioning
confidence: 99%